Quién construye la nación? Obreros y militares en el Astillero Río Santiago (1969-1979) (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2022)
This book seeks to illuminate the minor conjugations of social and labor relations in order to understand the plots of the repressive within the illegal and clandestine detention structure of the Argentine Navy in the period 1976-1983, based on the study of the Fuerza de Tareas 5 based in the Santiago River region, Buenos Aires.